Numerical solution of singular and non singular integral equations - Saleh, M.H.; Mohammed, D.Sh. (CUBO, A Mathematical Journal, 2013)
This paper is devoted to study the approximate solution of singular and non singular integral equations by means of Chebyshev polynomial and shifted Chebyshev polynomial. Some examples are presented to illustrate the method.